Career after successful medical board examination in general practice – a cross-sectional survey (Swiss Medical Weekly, 2013)
QUESTION UNDER STUDY: Switzerland is facing a shortage of general practitioners (GPs). Knowledge of the factors influencing career choice is crucial for increasing the attractiveness of general practice. The aim of our study was to report the working conditions of recently certified GPs and the effect of vocational training in general practice on GP skills and knowledge, and economic skills. Furthermore, we recorded when GPs chose general practice as a career, as well as potential barriers to and facilitators of their decision. METHODS: Study design: Cross-sectional survey with an online-based questionnaire. Study group: 1,133 physicians certified in general practice between the years 2000 and 2010. RESULTS: The response rate was 40.6% (456); 426 (44.1% females) were included in further analysis. A total of 341 (80.0%) were currently working in general practice. Female GPs were significantly more often employed (rather than working independently), working part-time and in group practices. Fifty-two (12.2%) of the participants did not work in general practice although they had intended to earlier. The majority (54.3%) of the participants working as GPs decided to become a GP during their residency. Overall, 60.6% of all participants completed vocational training in a general practice, which significantly improved self-perceived general practice skills compared with their colleagues without such training. CONCLUSIONS: Residency is a more important time-period than medical school for career decisions to become a GP. Attractive residency programmes must be developed to engage physicians in this vulnerable phase. The workplace settings of female GPs were significantly different from those ofmale GPs. Vocational training in general practice had a positive effect on self-perceived GP skills.